Towards a Framework for Anti-corruption and Improved Procurement Governance in Uganda .The Role of Administrative Efficiency. - BC, Basheka; C J, Auriacombe (Administratio Publica, 2021)
Public procurement has been and remains a core function of the public sector. When it is managed effectively and efficiently, it can contribute immensely towards attaining good governance within the now-complex public sector systems. This is due to a number of reasons. First, public procurement is a large contributor to government resource expenditure. When such resources are put to good use, it is expected to render a positive impact. Second, public procurement facilitates the attainment of broader government goals through its acquisition functions. Third, in most countries, public procurement as a key of corruption has been perpetuated, which has led to a leakage of public resources that would otherwise be devoted to service delivery. This article argues that promoting administrative efficiency, which will be a function of implemented governance structures, processes, values and mechanisms, is a likely panacea to procurement governance challenges. To this end, the article develops a framework to address public procurement-related corruption through improved governance. The framework is based on the underlying philosophy that the challenges relating to corruption in public procurement are built on a broader system of corruption within the entire administrative system of government. As such, any efforts to improve the efficiency and effectiveness of the public procurement function ultimately needs to be anchored on a broader governmentwide administrative systems improvement strategy.